Plan your defence - North, Freddie (Batsford bridge series.; How to play bridge (London, England), 1998)
The "How to Play Bridge" series provides a complete course of systematic home instruction for the beginner or aspiring player of any age. Each volume is imaginatively designed in two colours throughout and is full of tips and self-testing quizzes.